2017
DOI: 10.1007/s10495-017-1429-4
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of apoptosis: clinical implications in cancer

Abstract: Inhibitor of apoptosis (IAP) family comprises a group of endogenous proteins that function as main regulators of caspase activity and cell death. They are considered the main culprits in evasion of apoptosis, which is a fundamental hallmark of carcinogenesis. Overexpression of IAP proteins has been documented in various solid and hematological malignancies, rendering them resistant to standard chemotherapeutics and radiation therapy and conferring poor prognosis. This observation has urged their exploitation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
116
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(118 citation statements)
references
References 275 publications
1
116
0
1
Order By: Relevance
“…Apoptosis is an essential process for the homeostasis of multicellular organisms. Strict regulation of apoptosis plays a vital role in cancer . There are two main pathways of apoptotic cell death: one involves interactions of cell surface receptors, such as Fas and tumor necrosis factor‐α1, with their ligands, whereas the second pathway involves the mitochondria .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apoptosis is an essential process for the homeostasis of multicellular organisms. Strict regulation of apoptosis plays a vital role in cancer . There are two main pathways of apoptotic cell death: one involves interactions of cell surface receptors, such as Fas and tumor necrosis factor‐α1, with their ligands, whereas the second pathway involves the mitochondria .…”
Section: Discussionmentioning
confidence: 99%
“…Strict regulation of apoptosis plays a vital role in cancer. 12 There are two main pathways of apoptotic cell death: one involves interactions of cell surface receptors, such as Fas and tumor necrosis factor-α1, with their ligands, whereas the second pathway involves the mitochondria. 13 We used flow cytometry to detect apoptosis in GC cell lines with knocked down LRRN1, and the results showed that knocking down LRRN1 enhanced the apoptosis of GC cells.…”
Section: Discussionmentioning
confidence: 99%
“…New research confirms that receptor for advanced glycation endproduct (RAGE) can specifically deliver DADS into three negative breast cancer cells and significantly enhance the cytotoxicity of DADS by reducing anti-apoptotic proteins and upregulation of pro-apoptotic protein [72]. The researchers have found that DADS-RAGE-SLN can be obviously absorbed by MDA-MB231 and upregulate the expression of pro-apoptotic proteins (Bax, caspase-3, and caspase-9) and downregulate the expression of antiapoptotic proteins, such as Bcl-2 family (Bcl-2, Bcl-xl, Mcl-1) and survivin through the experiment of establishing the model of solid lipid nanoparticles with DADS-loaded solid lipid location nanoparticles (DADS-SLN), and DADS-loaded solid lipid location nanoparticles with the RAGE positioning (DADS-RAGE-SLN) [72]. In fact, caspase-3 plays an important role as the central effector for initiation of apoptosis [73].…”
Section: Activation Of the Apoptotic Pathways By Dadsmentioning
confidence: 90%
“…Survivin has the potential to suppress both extrinsic and intrinsic apoptotic pathways. XIAP is the most powerful suppressor for caspases (Mohamed, Bishr, Almutairi, & Ali, ). The rate of expressions for various apoptotic and anti‐apoptotic factors involved in both apoptotic pathways is changed in HCC (Breinig, Schirmacher, & Kern, ) (Figure ).…”
Section: Introductionmentioning
confidence: 99%